Freire and Lacan: Critical pedagogy as a radical methodology of the subject - Armonda, Alex J. (The Review of education/pedagogy/cultural studies, 2022)
Turning to key texts of Paulo Freire and Jacques Lacan, this paper argues that the experience organized in critical pedagogy can be rearticulated on the basis of a structural-practical connection to psychoanalysis. I pay specific attention to the methodical parallels that develop between the accounts of the psychoanalytic and pedagogical encounters in Lacan and Freire, arguing that critical pedagogy can be presented in a way that embraces the Lacanian theories of subjectivity and the unconscious, while affirming its political and emancipatory commitments. This theoretical analysis unfolds in two parts. First, I develop an account of Lacan that can militate for the critical pedagogical intervention, offering a grammar for elaborating upon Freire's claim that critical pedagogy be understood as kind of psychoanalysis. Bringing into focus a more practically oriented Lacan, I demonstrate how his work offers a rationality for organizing an intervention in the terrain of subjectivity. Second, I apply this reading of Lacan to the pedagogical experience defined by Freire in an effort to articulate in a new key the problems and possibilities structuring his intervention, linking the question of educational praxis to traumatic/unconscious knowledge as the site of operation for facilitating the political subjectivation of students.